Trends in ultrasound examination in family practice - Ali F. Alamri; Israr Khan; Mirza I. A. Baig; Rahila Iftikhar (Wolters Kluwer Medknow Publications, 2014)
Background: Ultrasound examination is very frequently used for the evaluation of abnormalities in various organs of the body. Our aim was to determine whether the requests by family physicians (FPs) for ultrasound examinations were appropriate. Our secondary objective was to enumerate positive and negative ultrasound reports for various diagnostic indications. Materials and Methods: This cross-sectional study was conducted during the period of month between June and August 2010, at the Family Medicine Department of North West Armed Forces Prince Salman Hospital, Tabuk. We reviewed the ultrasound requests of all patients included in this study and the findings of the procedure. Data were analyzed using the Statistical Package for the Social Sciences (SPSS Inc., Chicago, IL), version 16.0. Results: The requests and reports of 815 patients for ultrasound were reviewed. Females comprised 58.7% of the referred cases. The mean age of the sample at referral was 30 ± 18.5 for females and 34 ± 20.7 for males. Only 46% of the request forms contained conclusive information and instructions. Abdominal/pelvic ultrasounds were the most frequently requested; Nearly 71.2% of the ultrasound scans were normal. Abdominal/pelvis ultrasound was more likely to be reported as normal than ultrasound scans of other regions ( P = 0.007). Patients aged 41-60 years were more likely to have an abnormal ultrasound (P = 0.02). Conclusion: Our findings suggest that FPs have to be educated about imaging referral protocols in order to achieve better outcomes.